2003
DOI: 10.4049/jimmunol.170.11.5445
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Toll-Like Receptor 4 by Lipopolysaccharide During Cellular Invasion by Live Salmonella typhimurium Is a Critical But Not Exclusive Event Leading to Macrophage Responses

Abstract: Invasion of macrophages by salmonellae induces cellular responses, with the bacterial inducers likely to include a number of pathogen-associated molecular patterns. LPS is one of the prime candidates, but its precise role in the process, especially when presented as a component of live infecting bacteria, is unclear. We thus investigated this question using the lipid A antagonist E5531, the macrophage-like cell line RAW 264.7, and primary macrophage cultures from C3H/HeJ and Toll-like receptor 4−/− (TLR-4−/−) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 54 publications
4
67
0
Order By: Relevance
“…11 Finally, it has been shown that LPS is the main PAMP mediating Salmonellainduced production of tumor necrosis factor-a and nitric oxide by infected macrophages. 12 Knowing the importance of Tlr4 in the mouse model of Salmonella infection, we are interested in investigating how changes in the level of expression of Tlr4 impact on the mouse response to this pathogen. To address this question, we previously generated four lines of Tlr4 transgenic mice carrying various copy numbers of this gene on a C57BL10/ScNCr (B10/ScNCr) Tlr4 null background.…”
Section: Introductionmentioning
confidence: 99%
“…11 Finally, it has been shown that LPS is the main PAMP mediating Salmonellainduced production of tumor necrosis factor-a and nitric oxide by infected macrophages. 12 Knowing the importance of Tlr4 in the mouse model of Salmonella infection, we are interested in investigating how changes in the level of expression of Tlr4 impact on the mouse response to this pathogen. To address this question, we previously generated four lines of Tlr4 transgenic mice carrying various copy numbers of this gene on a C57BL10/ScNCr (B10/ScNCr) Tlr4 null background.…”
Section: Introductionmentioning
confidence: 99%
“…3B) was ineffective in controlling the infection. Although the lack of TLR4-dependent iNOS stimulation (25,26) can be compensated by the addition of IFN-␥ in vitro ( Fig. 2A), this necessitates a costly delay in macrophage activation until the arrival of cytokine-producing cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These nod-2 Ϫ/Ϫ mice are phenotypically similar to those generated and described by Kobayashi et al (9). Primary BMM were isolated from the femur and tibia of mice killed by cervical dislocation and cultured in RPMI 1640, 10% FCS, 5% horse serum, 2 mM Lglutamine, 1 mM sodium pyruvate, 10 g/ml gentamicin, and 20% supernatant taken from L929 cells (28). Before the experiments, cells were plated onto 96-well plates at a plating density of 2 ϫ 10 5 /well.…”
Section: ϫ/ϫmentioning
confidence: 99%